Prevalence of early childhood caries (ECC) and determining the risk of injury in children aged)3-6( years in Lattakia - زريقي سميره; ديوب يارا (Latakia University Journal -Medical Sciences Series, 2022)
Introduction: Despite the existence of a number of preventive measures against caries infection, dental caries remains one of the most prevalent infectious diseases in the world; Causes of early childhood caries: unmodifiable causes (genetic, social, economic) modifiable causes: (food habits, oral health). Early childhood caries affect many teeth and develop rapidly after eruption at 2.5 years of age, localized on the smooth surfaces of the maxillary temporal incisors and the occlusal surfaces of the temporal first molars. Objective: Knowing prevalence of ECC and determining its risk by assessing the dmft index (deacy, missing, filling) in children aged 3-6 years in Lattakia city. Materials and Methods: The total number of children examined was 1500 children, 75 children had early childhood caries, 25 cases were included in the study, 15 cases were excluded (did not meet the admission criteria) 35 cases were excluded due to (parents refused) in addition to 25 health witness cases, sample included children attending the Pediatric Department at Tishreen University Hospital – Lattakia. The case of caries was recorded based on the dental caries index (dmft), which aims to determine the number of decayed, restored or missing teeth due to caries. After obtaining the informed consent of the parents, then the data were collected and subjected to statistical analysis using the program spss statistical version 25. Results: The results showed that the prevalence of early childhood caries was 5%, the average dmft index values for children with early childhood caries were 7.20 ± 3.62 at a confidence level of 95%, where the mean dmft for the children of the studied sample, respectively, at the age of 3 years (66.6±1.63) At 4 years old (10.25±3.99), at 5 years old (5.4±2.07), and at 6 years old (5.16±3.37). Conclusion: The results of our research showed relatively low prevalence rates of early childhood caries, while 76% of the examined sample had a high risk of developing caries. These rates were associated with both qualification and night feeding, as our results did not show any significant difference between the two groups according to age or sex.